Flexing, the Fake Rich Phenomenon - Nanang Qosim Yusuf; Dewi Umronih Yusuf (International Journal Labs, 2024)
Of course everyone wants to be rich and to achieve it, but fake rich is a phenomenon that is now unconsciously holding young people hostage, this term is more appropriate is